Memprediksi Produksi Boba Di Xing Fu Tang Di Centre Point Mall Medan Mengguanakang Metode Fuzzy Mamdani - Sanjaya, Roma (Jurnal Kajian Ilmiah Teknologi Informasi dan Komputer, 2022)
PT. BOBA BAHAGIA MEDAN or known as XING FU TANG is an outlet that sells BOBA drinks, after the success of its first grand opening in 2018 last year at Lippo Plaza Mall Medan. Now it has several outlets in Medan Malls, one of which is at Center Point Mall Medan. With sales that can be said to be quite busy at one of the outlets in Center Point Mall Medan. Of course it is very interesting to do research with the title "Predicting BOBA Production at XING FU TANG CENTER POINT MEDAN Using the Fuzzy Mamdani Method". Having a problem formulation such as in determining the amount of Boba production in accordance with sales every day. The purpose of this study is to find out how the predictions for producing boba are in accordance with sales and existing stock of goods, so that there is no overstock of boba. This study uses the library method, observation and direct interviews with the management of Xing Fu Tang Center Point Mall Medan. The existing data sources were obtained directly from the company where the research was conducted. And the data was analyzed using the Mamdani Decision Support System and Fuzzy Method. The theoretical basis used in this study is to describe theories related to Decision Support Systems and the Mamdani Fuzzy Method. From the research conducted, it can be concluded that Xing Fu Tang Center Point Mall Medan is very concerned about producing Boba so that there are no mistakes and excess stock which can be very influential for the company, because Boba that has been produced must be sold immediately and cannot stay overnight because it will affect the taste. the taste of boba itself and the fatal thing is that it can cause losses to the company